WHEN INTOLERANT LANGUAGE CROWDS THE FEED: HOW DIGITAL DISCOURSES RECONSTRUCT RELIGIOUS FREEDOM IN INDONESIA - Hanipah, Heni; Djou, Dakia N.; Muslimin (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2025)
This study explores how intolerant language circulating on TikTok and Instagram reshapes public understandings of religious freedom in Indonesia. Although previous research has mapped hate speech forms or explored media–religion relations, few studies have integrated linguistic, pragmatic, and ideological analyses to explain how intolerance operates as symbolic power in digital environments. This research addresses that gap by analysing how intolerant expressions are produced, circulated, and interpreted within high-engagement online controversies. The study employs a descriptive qualitative design using Critical Discourse Analysis and social pragmatics. The dataset consists of 480 comment units from 130 public accounts on TikTok, Instagram, and X, complemented by 12 online news texts collected between January 2023 and August 2025. Analytical procedures include linguistic categorisation, pragmatic mapping of speech acts, and ideological interpretation of discursive power. The findings show, first, that intolerant language functions as a symbolic authority that reinforces moral hegemony and marginalises alternative religious viewpoints. Second, algorithmic amplification shifts religious freedom from a rights-based principle toward a visibility-driven performance shaped by emotional engagement. Third, counter‑discourses promoting respect and equality receive limited circulation, indicating an asymmetrical discursive ecology. These results suggest that digital platforms not only host but also structure negotiations of religious freedom. The study concludes that strengthening critical linguistic literacy and improving content governance are essential for safeguarding pluralism in Indonesia’s digital public sphere. Abstrak Penelitian ini mengkaji bagaimana bahasa intoleran yang beredar di TikTok dan Instagram membentuk ulang pemahaman publik mengenai kebebasan beragama di Indonesia. Meskipun penelitian sebelumnya telah memetakan bentuk ujaran kebencian atau menelaah hubungan antara media dan agama, hanya sedikit studi yang mengintegrasikan analisis linguistik, pragmatik, dan ideologis untuk menjelaskan bagaimana intoleransi beroperasi sebagai kekuatan simbolik dalam lingkungan digital. Penelitian ini mengisi kekosongan tersebut dengan menganalisis bagaimana ekspresi intoleran diproduksi, disirkulasikan, dan ditafsirkan dalam kontroversi daring yang memiliki tingkat interaksi tinggi. Studi ini menggunakan desain kualitatif deskriptif dengan pendekatan Analisis Wacana Kritis dan pragmatik sosial. Dataset terdiri atas 480 unit komentar dari 130 akun publik di TikTok, Instagram, dan X, dilengkapi dengan 12 teks berita daring yang dikumpulkan antara Januari 2023 hingga Agustus 2025. Prosedur analisis meliputi kategorisasi linguistik, pemetaan tindak tutur secara pragmatik, dan interpretasi ideologis terhadap dinamika kekuasaan dalam wacana. Temuan menunjukkan, pertama, bahwa bahasa intoleran berfungsi sebagai otoritas simbolik yang memperkuat hegemoni moral dan meminggirkan pandangan keagamaan alternatif. Kedua, amplifikasi algoritmik menggeser kebebasan beragama dari prinsip berbasis hak menuju performativitas yang ditentukan oleh visibilitas dan resonansi emosional. Ketiga, wacana tandingan yang mempromosikan rasa hormat dan kesetaraan memperoleh sirkulasi yang terbatas, menandakan ekologi wacana yang tidak seimbang. Hasil penelitian menunjukkan bahwa platform digital tidak hanya menjadi ruang ekspresi, tetapi juga struktur yang membentuk negosiasi kebebasan beragama. Studi ini menyimpulkan bahwa penguatan literasi linguistik kritis dan peningkatan tata kelola konten sangat penting untuk menjaga pluralisme dalam ruang publik digital Indonesia